2011
DOI: 10.1111/j.1365-2214.2011.01232.x
|View full text |Cite
|
Sign up to set email alerts
|

An exploration of parents' and young people's perspectives of hospice support

Abstract: Parents value a model of care that provides holistic, family-focused support that is responsive to individual needs and which promotes control and active involvement in decision making. The key challenge now is to respond to increasing need and a changing population of users.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
84
1
5

Year Published

2012
2012
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(93 citation statements)
references
References 13 publications
(16 reference statements)
2
84
1
5
Order By: Relevance
“…This is consistent with previous qualitative and survey research detailing the benefits of respite care for these families. 3,4,10,12,13 The current research findings are contrary to longitudinal studies that showed no significant benefit of respite on the mental health of caregivers of children with life-threatening conditions. 14,15 Discrepant findings may be due to the different time points in which data were collected.…”
Section: Discussioncontrasting
confidence: 99%
“…This is consistent with previous qualitative and survey research detailing the benefits of respite care for these families. 3,4,10,12,13 The current research findings are contrary to longitudinal studies that showed no significant benefit of respite on the mental health of caregivers of children with life-threatening conditions. 14,15 Discrepant findings may be due to the different time points in which data were collected.…”
Section: Discussioncontrasting
confidence: 99%
“…Unfortunately, referral to hospice services for this group was often delayed. Although this delay may in part be explained by parental reluctance to avail of hospice care as they associate this with the immediate end of life,27 28 our evidence also suggests a failure to inform parents of their entitlement to hospice care and that such services existed. Late referral created significant problems, in that a therapeutic relationship was formed over a shorter period of time, when the child was close to the end of life and with their family in a period of acute crisis.…”
Section: Discussionmentioning
confidence: 80%
“…This should not be mistaken for lack of understanding of their illness. A parent interviewed in an examination of how families are supported in hospice was surprised to find that ‘children were there to live, to have the best time possible’ [31]. The same study found that young people with terminal illness want to go out and meet other children who are not ill.…”
Section: Desire To Continue Livingmentioning
confidence: 99%